Student activation and active learning - Tamborra, Irene (Improving University Science Teaching and Learning, 2023)
Student activation and active learning have been proposed as tools through which students acquire knowledge and develop problem-solving skills. On the other hand, traditional teaching is still preferred in Physics courses with abstract and theoretical content. By employing student activation, I intend to explore whether the latter improves the student performance in theoretical courses.